Mechanism of Stability Enhancement for Adiponitrile High Voltage Electrolyte System Referring to Addition of Fluoroethylene Carbonate - Fang, Zhao; Zheng, Zekun; Cheng, Wudan; Zhang, Xingliang; Zhong, Kenan; Li, Linbo (Frontiers in Chemistry, 2020)
In order to improve the stability of high voltage electrolyte for 5 V-level LiNi0.5Mn1.5O4 cathode material, adiponitrile (ADN) with high oxidation stability was selected as the main solvent, meanwhile, 2% fluoroethylene carbonate (FEC) as the additive with good film forming effect was also used. And then, the effect of 2 mol L−1 LiBF4-GBL/ADN+2% FEC on the electrochemical performance of LiNi0.5Mn1.5O4 was explored at room temperature. The electrolyte system containing FEC can improve the cycle stability of the battery. At 1 C rate, the cycle capacity retention rate can reach 83% after 100 cycles, while the capacity retention rate of the electrolyte system without FEC and the ordinary commercial electrolyte system is only 77 and 68%, respectively. Besides, the rate performance of the battery with the addition of FEC also shows excellent performance, however, this kind of advantage is not obvious under the conditon of large rate. In addition, under the conditon of the synergistic effect between adiponitrile and fluoroethylene carbonate, the high-voltage electrolyte exhibits the good compatibility and lithium reversibility in the full cell with Li4Ti5O12 as the negative electrode.